Malocclusion-Related Quality of Life Questionnaire (MRQoLQ): Development and validation of a new psychometric tool for older adolescents with malocclusion - Elbe Peter; Radha Madhavanpillai Baiju; Remadevi Shivaraman; Netiyatt Ommen Varghese; Jolly Mary Varughese (Dental Press Editora, 2020)
ABSTRACT Objective: To develop and validate a new psychometric tool for assessing malocclusion-related quality of life among older Indian adolescents. Methods: Item generation involved analysis of existing validated tools, followed by development of new items using various qualitative steps. A draft item pool of 41 questions was initially generated and subjected to item reduction through sequential steps involving two clinical studies to ensure reliability and validity. 431 subjects aged between 15 to 18 years took part in the validation study. Principal component analysis with varimax rotation was performed to get a psychometric tool with good factorial structure and maximum variance. Results: Rotated component matrix resulted in a 20 item psychometric tool containing 4 domains with a total variance of 61.57%. Inter item, item total correlation and Cronbach α (α = 0.88) ensured good reliability. A positive correlation of the scale with global question ensured convergent validity. Independent t test showed statistically significant difference (p< 0.05) between mean score of IOTN-DHC and DAI with MRQoLQ, ensuring good construct validity. Conclusions: The newly developed psychometric tool is named as Malocclusion-Related Quality of Life Questionnaire (MRQoLQ) having 20 questions, including 2 socioeconomic items. The scale showed good reliability and initial validity, hence can be used among older adolescents with malocclusion to assess their malocclusion-related quality of life.